Effects of anthropometric towards interface pressure variables and design optimization on the car seat - Nabilah Sabri,; Nor Kamaliana Khamis,; Chun, Tee Ng; Mohd Faizal Mat Tahir,; Jailani Besar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The design optimisation of car seats is vital in ensuring comfort and safety whilst driving. The main aim of this study is to determine the relationship between anthropometric parameters, interface pressure on car seats and driver’s safety in a preferred driving position. A pressure-map sensor was used to identify the pressure patterns on the car seat. Results indicate significant relationships were found between interface pressure of car seat and certain anthropometrics dimension. A strong correlation was established amongst body mass, body mass index and interface pressure at certain body parts, with r of nearly 0.50. Majority of the anthropometric dimensions and interface pressure show medium correlations between 0.31 and 0.49. The established relationship helps to estimate the perceived comfort and safety related to the car seat design. Hence, this guideline can help to prevent driver’s fatigue by considering the elements of anthropometrics and interface pressure in the car seat design.